Enzymatic hydrolysis of spent saccharomyces cerevisiae derived from sago bioethanol fermentation - Nik, Nur Aziati Mahmod; Nurashikin, Suhaili; Husaini Awang, Ahmad Sallehin Awang; Awang Adeni, Dayang Salwani; Ashari, Siti Efliza (World Researchers Associations, 2023)
Spent Saccharomyces cerevisiae is a by-product of bioethanol fermentation. The spent yeast is abundant in valuable components which can be used for many applications. One of the ways to prepare yeast extract is through enzymatic hydrolysis which is by rupturing the yeast cell walls using exogenous enzymes under certain conditions that promote the leakage of intracellular compounds. To date, enzymatic hydrolysis of spent S. cerevisiae derived from the production of sago bioethanol is yet to be thoroughly explored. In the present study, we examine the feasibility of enzymatic hydrolysis of spent S. cerevisiae generated from sago bioethanol fermentation. The effect of two enzymes namely alcalase and cellulase and their concentrations (0.1-0.5% (v/v) on the release of protein and carbohydrate in the hydrolysate was also investigated.